Pengaruh Rasio Likuiditas, Solvabilitas, dan Profitabilitas terhadap Kesehatan Keuangan PT Merdeka Copper Gold Tbk. - Cindy Grace Mendrofa; Dewi Armanda Parhusip; Priscilla C.M Simorangkir; Hamonangan Siallagan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to see the effect of financial ratios on the financial health of PT Merdeka Copper Gold Tbk. in the period 2022 to 2023. The analysis was carried out using liquidity, solvency, profitability ratios. The data source in this study is secondary data, namely the financial statements of the company PT Merdeka Copper Gold Tbk for the period 2022-2023. The type of research used in this research is a quantitative method using descriptive studies. The results of the calculation of the liquidity ratio are used to meet cash needs when these needs increase in meeting short-term obligations, the solvency ratio to measure the extent to which the company's assets are financed from debt, and the profitability ratio to assess the company's ability to achieve profits. The results of this calculation show significant changes in several financial ratios that illustrate the company's financial condition, the factors that influence it, and the implications for management and investor decision making.